Sharia incorporated : a comparative overview of the legal systems of twelve Muslim countries in past and present - Otto, Jan Michiel, 1952- (Law, governance, and development. Research., 2010)
Comparative analysis of sharia and its relation to national law in a broad range of Muslim countries.